Miscellanea Celtica in memorian Heinrich Wagner - Mac Mathuna, Seamus; Wagner, Heinrich, 1923-; O Carrain, Ailbhe (Uppsala : Uppsala University, 1997)
Papers in English, German, and Irish
Includes bibliographical references
Keywords: Celtic philology; Celtic literature -- History and critism